Disaster Preparedness in Sri Lankan University Libraries: Before COVID-19. Issue 3 (3rd July 2021) - Wijayasundara, Nayana Darshani
ABSTRACT: This study explores the necessity of developing disaster risk reduction plans and increasing the level of preparedness for disasters for academic libraries in Sri Lanka. It examines some of the different types of disasters; natural, man-made, and hybrid, which can occur in university libraries. Informants were the librarians of all 15 Sri Lankan state universities. The methodology is mixed-method with data gathered through questionnaires and interviews. In this study, the researcher considered the likelihood of occurrence of various types of disaster and their potential impact on university libraries. The results reveal that fire is the most expected disaster. Results highlight the importance of disaster risk reduction plans for university libraries and emphasise that every library should adopt a plan to safeguard its legacy. This study was conducted in 2019, thus infectious diseases were identified as an 'unlikely to occur' disaster category. However, events of 2020 and the COVID-19 pandemic, indicate a need for librarians to also rethink providing continuous library services during disasters such as pandemics.